Edukasi Preventif Anti Perundungan dalam Mewujudkan Lingkungan Sekolah Aman di SD Muhammadiyah Merangin - Putri, Riska Meisyi; Izhar, Muhammad Futaki; Aprizal, Muhammad; Mardalena (Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying is a serious problem still found in elementary schools and has the potential to hinder the psychological, social, and academic development of students. Students' low understanding of the forms, impacts, and consequences of bullying is a factor that drives the importance of early prevention efforts through an educational approach. This Community Service activity aims to increase students' understanding and awareness of bullying behavior as a preventive measure in creating a safe and conducive school environment. The method of implementation of the activity is carried out through preventive education which includes delivering material on the concept and types of bullying, interactive discussions with students, and the use of educational media adapted to the characteristics of elementary school students. The activity was carried out at Muhammadiyah Merangin Elementary School with the main target of students. The results of the activity showed an increase in students' understanding of bullying, the growth of empathy, and awareness to reject and prevent bullying behavior in daily interactions in the school environment. Students also showed a positive response and active participation during the educational process. Based on these results, it can be concluded that preventive anti-bullying education significantly contributes to building student awareness and supporting the creation of a safe, comfortable, and bullying-free school environment.